MTORC1-mediated NRBF2 phosphorylation functions as a switch for the class III PtdIns3K and autophagy. Issue 3 (4th March 2017) - Ma, Xi; Zhang, Shen; He, Long; Rong, Yueguang; Brier, Livia Wilz; Sun, Qiming; Liu, Rong; Fan, Weiliang; Chen, She; Yue, Zhenyu; Kim, Joungmok; Guan, Kun-Liang; et al.
ABSTRACT: NRBF2/Atg38 has been identified as the fifth subunit of the macroautophagic/autophagic class III phosphatidylinositol 3-kinase (PtdIns3K) complex, along with ATG14/Barkor, BECN1/Vps30, PIK3R4/p150/Vps15 and PIK3C3/Vps34. However, its functional mechanism and regulation are not fully understood. Here, we report that NRBF2 is a fine tuning regulator of PtdIns3K controlled by phosphorylation. Human NRBF2 is phosphorylated by MTORC1 at S113 and S120. Upon nutrient starvation or MTORC1 inhibition, NRBF2 phosphorylation is diminished. Phosphorylated NRBF2 preferentially interacts with PIK3C3/PIK3R4. Suppression of NRBF2 phosphorylation by MTORC1 inhibition alters its binding preference from PIK3C3/PIK3R4 to ATG14/BECN1, leading to increased autophagic PtdIns3K complex assembly, as well as enhancement of ULK1 protein complex association. Consequently, NRBF2 in its unphosphorylated form promotes PtdIns3K lipid kinase activity and autophagy flux, whereas its phosphorylated form blocks them. This study reveals NRBF2 as a critical molecular switch of PtdIns3K and autophagy activation, and its on/off state is precisely controlled by MTORC1 through phosphorylation.